Comparison of placental grading at different periods of gestation in PIH patients and their outcome - S., Sneha; S., Sreelatha; Ramaiah, Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The current study follows grannum grading of placenta. It is well known that there is accelerated placental maturation in PIH patients and the ultrasonic appearance of grade 3 placenta before 37 weeks may signify placental dysfunction and is associated with development of low birth weight babies, IUGR meconium stained liquor, low APGAR score. Hence this study was conducted to emphasize on placental grading at different periods of gestation to predict and prevent increased obstetric and fetal compromise and to compare the outcomes. Methods: Obstetric scans were performed in all PIH patients attending antenatal OPD and inpatients at ESIC and PGIMSR medical college, Bangalore to know the placental grading and biophysical profile. These women were followed till their delivery for obstetric and fetal outcomes. Results: Grade 3 placenta is seen in 17 patients in group 1(50%) and 39 patients (59%) in group 2. For statistical analysis grade 1 and 2 were combined and compared with grade 3. P-value 0.198 which was not statistically significant. There was no statistically significant difference in age and gravidity between two groups. The medical disorders were more in group 2 i.e., between 37 - 40 weeks. The complications of PIH were also more in group 2. There were more number of LSCS (n=19 versus 14) in 34-36 weeks group which was not statistically significant. Fetal outcomes like IUGR and IUD were more in group 2 which was not statistically significant. The mean birth weight in group 1 was 2 kg as compared to 2.7 kg in group 2. All associated medical disorders were more in group 2. Conclusions: In hypertensive women there is accelerated placental maturation leading to maternal and fetal complications. Hence women with accelerated placental maturity in ultrasound should be closely monitored and appropriately managed. However, we recommend larger randomized studies are necessary.